Study Heavy Concrete on Base Asphaltic Waste as A Small Aggregate - Rashidov Mirjaxongir; Gulomova Kh. (European Journal of Life Safety and Stability (2660-9630), 2022)
Waste asphalt blocks from construction sites are usually processed in the recycling plants to be used as recycled asphalt aggregates. These blocks are usually fed into the grizzly to break them into small pieces and to remove the soil attached on their surfaces. At present, the soil content of grizzly-under-materials does not satisfy the required standard value. The authors present the possibility to utilize some asphalt building waste materials to produce simple concrete. To prepare the mixes, Recycled Concrete Aggregate as a small aggregate of 0.16-5 mm fraction were used. Concretes with waste were mixed with 300 kg/m2 of four types of cements. The concrete sample specimens were tested for mechanical properties which are related to durability. After 28 days compressive strength increase to 45 MPa and after 90 days 50 MPa were achieved.